Effect of simulated dust storm conditions on the physiological features of wild pistachio - Hamid Reza Naji; Farshad Roushani Nia; Afsaneh Tongo; Forough Soheili; Ali Arminian (Forest Science and Technology, 2024)
AbstractDust storms are a common natural phenomenon in the world, especially in the arid and semi-arid regions of the world. This phenomenon, like other natural hazards, can have harmful effects on the plants. This study investigates the effects of dust under simulated conditions on the biochemical properties of wild pistachio (Pistacia atlantica). Two-year-old seedlings were provided by a state nursery. As a completely randomized design, seedlings were put in simulated dust chamber. The dust was applied at concentrations of 5000, 7000 and 9000 mg/m3 for 10 weeks with intervals of 12 days. At the same time, ten seedlings were selected as control seedlings. At the end of each dusting period, the leaves of the treated and control seedlings were collected from the middle part of the crowns and stored in the freezer for further analysis. The results showed a decrease in chlorophyll pigments and carotenoids with increasing dust concentration, while carbohydrates and catalase and peroxidase enzymes increased. No significant differences were observed in the proline content of the treated and control seedlings. This could be due to the short time of treatment as well as the intensity of the induced dust storm stress. In conclusion, the results can be considered as basic information on the variations of physiological characteristics of forest trees to natural dust storms and their adaptability to climatic changes.